2013
DOI: 10.5539/elt.v6n6p57
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Teachers’ Age, Gender and Experience on the Use of Information and Communication Technology in EFL Teaching

Abstract: The integration of information and communication technology (ICT) into language teaching and learning depends on many factors. Some of these factors are associated with teachers. Teachers play a crucial role in the integration of ICT. This study investigates the impact of teacher's age, experience, and gender on the integration of ICT into language teaching. This study utilized a mixed-method approach of investigation, which applies both qualitative and quantitative methods. The instruments used for data colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
17
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 11 publications
(28 reference statements)
8
17
2
2
Order By: Relevance
“…It is also a general believe that women are lagging behind when it comes to the use of ICT (Hallberg, Kulecho, Kulecho & Okoth, 2011). For example, male lecturers were found to use ICT facilities most as compared to their female counterparts (Mahdi & Al-Dera, 2013). Similarly, Tezci (2009) found significant influence of gender on the level of utilization of ICT facilities by teachers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also a general believe that women are lagging behind when it comes to the use of ICT (Hallberg, Kulecho, Kulecho & Okoth, 2011). For example, male lecturers were found to use ICT facilities most as compared to their female counterparts (Mahdi & Al-Dera, 2013). Similarly, Tezci (2009) found significant influence of gender on the level of utilization of ICT facilities by teachers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, studies have shown that older teachers are less confident with using computers as compared to their younger counterpart (Teo, Lee & Chai, 2008). While, some other studies have shown that age is not a determining factor in use of ICT in teaching (Mahdi & Al-Dera, 2013;Tezci, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Es destacable que, a pesar del amplio despliegue y repercusión social de este programa, no hayamos encontrado investigaciones al respecto. Pocos son también los estudios (Almerich, Suárez, Orellana, Belloch, Bo & Gastaldo, 2005;Cox, Preston & Cox, 1999;Kubiatko, 2013;Morris & Venkatesh, 2000;Saleh & Sa´ad, 2013;Torres, Robles & Molina, 2011) acerca de la influencia que tiene la edad sobre las decisiones para la adopción de la tecnología. En dichas investigaciones, focalizadas en estudios de caso diversos, se apunta la misma idea, es decir, la importancia que tiene la edad en la integración de las TIC en el proceso de enseñanza-aprendizaje, así como que el uso y actitudes del profesorado hacia éstas será distinto en función de la edad.…”
Section: Introducción Y Estado De La Cuestiónunclassified
“…Centrándonos en la edad, son varios los estudios que amparan la idea de que este factor incide directamente sobre el uso de las TIC (Kubiatko, 2013;Morris & Venkatesh, 2000;Torres et al, 2011). Otros estudios, aunque revelan un posible impacto del factor edad, lo consideran inferior al que puedan tener otros aspectos como es el género (Almerich et al, 2005;Saleh & Sa´ad, 2013).…”
Section: Introducción Y Estado De La Cuestiónunclassified